Disaster risk management in Asia and the Pacific - Davis, Ian (New York: Routledge, 2015)
This book is linked with two international frameworks-Millennium Development Goals and the Hyogo Framework for Action, a program focused on disaster risk management- to study the key trends in terms of disaster incidence, sources of vulnerability and social and economic challenges. The book will help readers understand the process better.
"ADBInstitute."
Includes bibliographical references and index.
usc 24/10/17
Loans
Keywords: Emergency management; Natural disasters; Risk management; Pacific Ocean--Islands of the Pacific; Asia